2018
DOI: 10.1123/japa.2017-0203
|View full text |Cite
|
Sign up to set email alerts
|

“Shall We Dance?” Older Adults’ Perspectives on the Feasibility of a Dance Intervention for Cognitive Function

Abstract: We explored perceptions of social dance as a possible intervention to improve cognitive function in older adults with subjective memory complaints. A total of 30 participants (19 females; mean age = 72.6 years; SD = 8.2) took part in the study. This included 21 participants who had self-reported subjective memory complaints and nine spouses who noticed spousal memory loss. Semistructured interviews were conducted, and a thematic analysis was used to analyze the data. Three main themes were constructed: (a) dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…Furthermore, dance was found to improve well-being and reduce stress, anxiety, psychological distress and fatigue. 25,41 Dancing constitutes a form of expression 33 and promotes social interaction, 24,42 which, on its own, is recognized to have beneficial effects on Dancing in the golden age 6 cognition. 43 Interestingly, older adults reported to be particularly attracted to dancing because a playful and spontaneous atmosphere enabled them to remember and 're-live' happy experiences from their youth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, dance was found to improve well-being and reduce stress, anxiety, psychological distress and fatigue. 25,41 Dancing constitutes a form of expression 33 and promotes social interaction, 24,42 which, on its own, is recognized to have beneficial effects on Dancing in the golden age 6 cognition. 43 Interestingly, older adults reported to be particularly attracted to dancing because a playful and spontaneous atmosphere enabled them to remember and 're-live' happy experiences from their youth.…”
mentioning
confidence: 99%
“…43 Interestingly, older adults reported to be particularly attracted to dancing because a playful and spontaneous atmosphere enabled them to remember and 're-live' happy experiences from their youth. 26,42 In summary, dance training is a form of physical exercise that increases physical function as well as social interaction and motivation. 19 However, to our knowledge only one study 32 has previously investigated the effects of dancing, based on a Caribbean style, in older Italian adults.…”
mentioning
confidence: 99%
“…Confidence to enjoy dancing with a person you do not know relates to several features that are fairly unique to dance including comfort with being in close physical contact with strangers and co-operation to co-ordinate movement with another person, tapping into social efficacy. While social dance provides the opportunity to socialiseidentified in dance research as a strong motivator to join and adhere to social dance programs (Coogan et al, 2021;Thøgersen-Ntoumani et al, 2018) -this can be achieved only in welcoming and relaxed social environments. While positively framed, the social dance efficacy item challenges the respondent to consider an aspect of dance participation which may compromise their social experience and impact motivation to participate.…”
Section: Task-based Dance Self-efficacy Itemsmentioning
confidence: 99%
“…Engaging older adults in effective and enjoyable physical activity programs to protect physical and cognitive health is a global research priority (World Health Organisation, 2017). Dance is accessible and appealing (Gordon-Nesbitt, 2020) exercise activity (Yan et al, 2018) which is cognitively challenging (Brown & Parsons, 2008) and enriched with music and social interaction (Brustio et al, 2018;Thøgersen-Ntoumani et al, 2018). Although enthusiasm for dance as a lifestyle intervention has inspired a substantial body of efficacy trials over the past decade, evidence supporting the health benefits of dance has been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological aspects include improved well-being which reduces stress, anxiety and psychological distress [13,14]. Interestingly, older adults reported that they found dancing to be an attractive social activity because the activity made them feel playful and "re-live" happy experiences from their youth [15,16]. Furthermore, social dance builds relationships between older adults through their partners, their friends and their families.…”
Section: Introductionmentioning
confidence: 99%